UiTM-UDM-UMP to jointly host NaSOS2009 - M. M., Yusoff; Saifful Kamaluddin, Muzakir; Nurul Nadia, Abd Razak; Safriza, Baharuddin; Muhammad Najib, Muhammad Nor; Noor Azhar, Abd. Rasid (Penerbit UMP, 2009)
JAN 22 KUALA TERENGGANU : In an effort to promote networking and collaboration in Organic Synthesis among chemistry researchers in the country, three Universities, namely, UiTM, UDM and UMP, agreed to jointly host the first such symposium in the country.